If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(4y + 2) = 0 Reorder the terms: 5(2 + 4y) = 0 (2 * 5 + 4y * 5) = 0 (10 + 20y) = 0 Solving 10 + 20y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + 20y = 0 + -10 Combine like terms: 10 + -10 = 0 0 + 20y = 0 + -10 20y = 0 + -10 Combine like terms: 0 + -10 = -10 20y = -10 Divide each side by '20'. y = -0.5 Simplifying y = -0.5
| -2m+10=4m-14 | | 0.9x-3.5=0.1 | | -2y-5=3y+20 | | u/3-12=29 | | x^(4/3)-10x^(2/3)=-9 | | 15+x+90=180 | | 32+2y=2(5y+8) | | x^4/3-10x^2/3=-9 | | 2(x-2)/3=2(x+4)/9 | | -7/-84 | | 2+3*(4-2)+6/3+2 | | 1050+600+5x=800+400+8x | | -x^2+4=y | | 3d+8=-4-(3-2d) | | a+5/a2-4-a+4/a2-4a+4 | | (37b-4)-9(4b+4)=-3 | | 3/4w=-48 | | Y=-4/3x+2 | | (14+2x)(22+2x)=884 | | 3-4w=-48 | | (22b-7)-7(3b+1)=-2 | | (-60+300x)+x=56 | | 2-3/8n=13 | | 6(y+2)-7=2(y-7) | | (14+2x)(22+2x)=0 | | 3(x+8)=5(x+3)-x | | 1/2(x+4)=5 | | 3(x+8)=5(x+3) | | 308+72x+4x^2=0 | | n-3/8n=13 | | 4.34/567.8 | | 2=x/10 |